2016
DOI: 10.1590/s1806-92902016001000009
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the selling prices of calves in auctions in Santa Catarina State, Brazil

Abstract: -The objective of this study was to investigate the effects of genetic group and calf sex on selling prices in auctions in the state of Santa Catarina (SC), Brazil. We evaluated 33,143 animals, representing 3,587 lots in 47 auctions from 2009 to 2014. The calves were classified according to genetic groups: British breed or crossbreed (BX); Continental breed or crossbreed (CX); Zebu breed or crossbreed (ZC); British and Continental crossbreed (BC); and Bos taurus and Bos indicus crossbreed (TI). The lots were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
(15 reference statements)
0
5
0
3
Order By: Relevance
“…We analyzed 2,432 batches of males and 1,880 batches of females (Table 5), in which the price paid for males was higher (15.75%) than that for females (P<0.05). Fornari et al (2016) evaluated auctions in the state of Santa Catarina in Brazil and found the average price of males was 6.78% higher than that of females. Koetz Júnior et al (2014) observed an 11.5% difference in the price of male calves in relation to females in the northern part of the state of Paraná, Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed 2,432 batches of males and 1,880 batches of females (Table 5), in which the price paid for males was higher (15.75%) than that for females (P<0.05). Fornari et al (2016) evaluated auctions in the state of Santa Catarina in Brazil and found the average price of males was 6.78% higher than that of females. Koetz Júnior et al (2014) observed an 11.5% difference in the price of male calves in relation to females in the northern part of the state of Paraná, Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by Crespo et al (2006) in Uruguay and by Troxel and Barham (2012) in the state of Arkansas, USA. According to Fornari et al (2016), the higher price paid for males may be related to the greater potential for weight gain during rearing and fattening, in addition to greater final value at slaughter. On the other hand, farmers generally purchase females for replacement of matrices, and they are sold at lower prices at the end of their reproductive life.…”
Section: Discussionmentioning
confidence: 99%
“…Livestock markets operate mainly through direct sales between buyers and sellers or auctions (Fornari et al, 2016). Sales of animals can result in longer transport times,…”
Section: Water Buffalo Welfare At Livestock Marketsmentioning
confidence: 99%
“…O preço de comercialização é definido por meio da interação de diversos fatores, estritamente relacionados à genética e ao fenótipo dos animais, tais como o peso, o sexo, a raça, a presença ou não de chifres, o tamanho e a uniformidade do lote (Schoroeder et al, 1988;Cristofari et al, 2008;Cristofari et al, 2009;Cristofari et al, 2010;Fornari et al, 2016), bem como sofre influência direta do preço praticado com outras categorias bovinas (Sachs e Martins, 2007), em especial as de animais para abate, e, mais recentemente, pelos preços praticados para exportação de bezerros vivos.…”
Section: Introductionunclassified